2015
DOI: 10.1155/2015/245459
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long-Term Intranasal Serotonin Treatment on Metabolic Parameters and Hormonal Signaling in Rats with High-Fat Diet/Low-Dose Streptozotocin-Induced Type 2 Diabetes

Abstract: In the last years the treatment of type 2 diabetes mellitus (DM2) was carried out using regulators of the brain signaling systems. In DM2 the level of the brain serotonin is reduced. So far, the effect of the increase of the brain serotonin level on DM2-induced metabolic and hormonal abnormalities has been studied scarcely. The present work was undertaken with the aim of filling this gap. DM2 was induced in male rats by 150-day high-fat diet and the treatment with low dose of streptozotocin (25 mg/kg) on the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 99 publications
3
29
0
2
Order By: Relevance
“…Given the beneficial role of the serotonin (5-HT) system in the enhancement of brain plasticity (Quesseveur et al, 2013), the possibility that deficits in 5-HT neurotransmission underlie the comorbidity between T2D/IR and depression, has been raised. Consistent with this hypothesis, decreased levels of tryptophan were detected in the CNS of patients with T2D (Kloiber et al, 2010;Herrera-Marquez et al, 2011) or in rodents fed an HFD (Kim et al, 2013;Derkach et al, 2015). Using intracerebral microdialysis, we showed that mice fed an HFD displayed lower basal hippocampal extracellular 5-HT concentrations (Zemdegs et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…Given the beneficial role of the serotonin (5-HT) system in the enhancement of brain plasticity (Quesseveur et al, 2013), the possibility that deficits in 5-HT neurotransmission underlie the comorbidity between T2D/IR and depression, has been raised. Consistent with this hypothesis, decreased levels of tryptophan were detected in the CNS of patients with T2D (Kloiber et al, 2010;Herrera-Marquez et al, 2011) or in rodents fed an HFD (Kim et al, 2013;Derkach et al, 2015). Using intracerebral microdialysis, we showed that mice fed an HFD displayed lower basal hippocampal extracellular 5-HT concentrations (Zemdegs et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…We found no significant difference between male and female rats ( Figure 4d). Female rats are reported to be no more variable than male rats across diverse traits relevant to neuroscience studies (Becker, Prendergast, & Liang, 2016), and female rats have been used for studies involving intranasal administration (Derkach, Bondareva, Chistyakova, Berstein, & Shpakov, 2015;Kumar et al, 2018). Thus, we used female rats for the subsequent intranasal administration studies.…”
Section: Compliance With Requirements For Studies Using Animalsmentioning
confidence: 99%
“…Indirect evidence, however, is in favour of an attenuation of serotonergic tone because decreased levels of free tryptophan were detected in the CNS of patients with T2DM (Kloiber et al, 2010;Herrera-Marquez et al, 2011). Accordingly, a significant decrease in plasma or brain levels of 5-HT has been reported in rodents after prolonged HFD exposure (Kim et al, 2013;Derkach et al, 2015), but these neurochemical changes have never been confirmed using in vivo microdialysis.…”
Section: Introductionmentioning
confidence: 99%